PENGARUH PENGAWETAN TERHADAP KEKUATAN DAN KEAWETAN PRODUK LAMINASI BAMBU - Aini, Nurul; Morisco, Morisco; Anita, Anita (Civil Engineering Forum Teknik Sipil, 2009)
The need of housing corresponds with the increasing population growth. Such condition affects the demand of timber used for building construction. On the other hand, the government extremly minimizes forest logging to protect the forest from degradation. To solve the problem of increasing need of timber, one of the efforts is by utilzing bamboo as local materials for laminated products. However besides the advantages, bamboo is a susceptible material for organism. Improving the durability of bamboo againts organism can be achieved through preservation.This research (study) is aimed to recognize the effect of bamboo preservation to the strength and durability of laminated bamboo. In this study, Petung bamboo (Dendrocalamus sp) was treated with boron plus 63% preservative with the concentration of 1.57% and 3.15% using Bouherie-Morisco method with 3 kg/cm2 and 4kg/cm2 air pressure. The glulam bamboos in 25 mm x 30 mm x 2000 mm dimension were made from preserved bamboo with polimer isocyanate adhesive in 50#/MSGL under 1.2 Mpa pressure. Untreated bamboo were used as control for each treatment, 3 aplications were applied. Results of this research showed that moisture content was affected by the preservation pressure. The preservation treatments were not affected by the density, compressive strength parallel to the grain, tensile strength parallel to the grain, internal bond strength, horizontal bending strength, vertical bending strength, horizontal modulus of elasticity, vertical modulus of elasticity of the tested glulam bamboo as well as retention of preservatives was affected by the concentration of preservatives or the pressure of the treatment. The treatment method affected the termites mortality percentage but not the mass lost percentage. The physical and mechanical properties of treated bamboo was not indefference to the untreated bamboo. There was a tendency that mass lost precentage in untreated bamboo was higher than in treated bamboo while the termite mortality percentage in treated bamboo was lower than un treated bamboo.